2015
DOI: 10.4236/aim.2015.512085
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Bacterial Group in Field Soil Evaluated by a Newly Developed Method Based on Restriction Fragment Length Polymorphism Analysis

Abstract: Spreading of antibiotic resistant bacteria into environment is becoming a major public health problem, implicating affair of the indirect transmission of antibiotic resistant bacteria to human through drinking water, or vegetables, or daily products. Until now, the risk of nosocomial infection of antibiotic resistant bacteria has mainly been evaluated using clinical isolates by phenotypic method. To evaluate a risk of community-acquired infection of antibiotic resistant bacteria, a new method has been develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 26 publications
0
25
2
Order By: Relevance
“…In the major MERFL, ratio of the MERFLs having 100% similarity to the corresponding theoretical MERFLs (62.9%; Table 3) was lower than that of the former study (90.5%) [1], and the ratio in the 2nd major MERFLs (13.5%; Table 3) having 100% similarity to the corresponding theoretical MERFLs was also lower than that of the former study (50.0%) [1]. This might be caused from a difference of used incubation media as the following; NB medium used in this study was not a selective medium, more diverse microorganisms were proliferated in the each MPN vials than that used in the former study, which made it more difficult to select the MERFLP digested from the homogeneous 16S rDNA among the mixed MERFL.…”
Section: Affiliation Of Bacteria By Merflp Without Isolationcontrasting
confidence: 45%
See 4 more Smart Citations
“…In the major MERFL, ratio of the MERFLs having 100% similarity to the corresponding theoretical MERFLs (62.9%; Table 3) was lower than that of the former study (90.5%) [1], and the ratio in the 2nd major MERFLs (13.5%; Table 3) having 100% similarity to the corresponding theoretical MERFLs was also lower than that of the former study (50.0%) [1]. This might be caused from a difference of used incubation media as the following; NB medium used in this study was not a selective medium, more diverse microorganisms were proliferated in the each MPN vials than that used in the former study, which made it more difficult to select the MERFLP digested from the homogeneous 16S rDNA among the mixed MERFL.…”
Section: Affiliation Of Bacteria By Merflp Without Isolationcontrasting
confidence: 45%
“…Although a number of Actinobacteria (E) was high after thermophilic phase, they were only detected in the two higher dilution vials (T10 −9 1H, M10 −11 2M, Table 1). Actinobacteria was also detected only in two vials in the former study [1]. As the recent research indicated that 16S rDNAs of some Actinobacteria and Firmicutes were not amplified by the used PCR condition, a numbers of Actinobacteria (E) in this study might be underestimated.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations